La ejecución presupuestaria y su efecto en el cumplimiento de objetivos de la municipalidad provincial de Trujillo, ejercicio 2018 - Baltodano Zelada, Maritza Rocio (2021)
This research is a work that aims to know how strategic planning allows the Provincial Municipality of Trujillo and, in general, any public entity to define its objectives and goals for a certain period and, based on this, develop its institutional budget based on said objectives goals, in this way the execution of said budget will allow an adequate approach to the fulfillment of the proposed objectives. The general objective of this research is to evaluate the budget execution of the Provincial Municipality of Trujillo and its effect on the fulfillment of its objectives and goals set for the 2018 period, in order to comply with it, an analysis of the modified institutional budget for the 2018 fiscal year was carried out. and of the strategic and operational plans applicable to said exercise, as well as a description of the strategic planning of the evaluated area, and finally an analysis of the execution of the budgeted expenses based on the objectives set; This in order to test the hypothesis raised: The budgetary execution of the Provincial Municipality of Trujillo has had a positive effect on the fulfillment of the objectives set for the 2018 financial year. From the analysis of the results obtained in the investigation, it was possible to contrast the hypothesis, concluding that the budget execution of the Provincial Municipality of Trujillo did not have a positive influence on the fulfillment of the objectives and goals proposed for the 2018 fiscal year.